1999
DOI: 10.1086/307523
|View full text |Cite
|
Sign up to set email alerts
|

Dust Absorption and the Ultraviolet Luminosity Density atz ≈ 3 as Calibrated by Local Starburst Galaxies

Abstract: We refine a technique to measure the absorption corrected ultraviolet (UV) luminosity of starburst galaxies using rest frame UV quantities alone, and apply it to Lyman-limit U -dropouts at z ≈ 3 found in the Hubble Deep field (HDF). The method is based on an observed correlation between the ratio of far infrared (FIR) to UV fluxes with spectral slope β (a UV color). A simple fit to this relation allows the UV flux absorbed by dust and reprocessed to the FIR to be calculated, and hence the dust-free UV luminosi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

187
2,279
22

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,129 publications
(2,488 citation statements)
references
References 82 publications
(134 reference statements)
187
2,279
22
Order By: Relevance
“…With a UV spectral index of β = −1.5 ± 0.8, we can surmise that the expected L IR /L UV ratio for SMGs would be around ∼10 if a dust attenuation relation with β from Meurer et al (1999) is assumed, but again, factors of ∼100 are more typical for SMGs. Reddy et al (2012) recently studied the direct dust luminosity of UV-selected galaxies, comparing the UV spectral slope directly to stacked Herschel flux densities in GOODS-Herschel and found that the attenuation and reddening of the slope agree with previous results calibrated from local starburst galaxies.…”
Section: Rest-frame Ultraviolet and Optical Spectral Characterizationmentioning
confidence: 89%
“…With a UV spectral index of β = −1.5 ± 0.8, we can surmise that the expected L IR /L UV ratio for SMGs would be around ∼10 if a dust attenuation relation with β from Meurer et al (1999) is assumed, but again, factors of ∼100 are more typical for SMGs. Reddy et al (2012) recently studied the direct dust luminosity of UV-selected galaxies, comparing the UV spectral slope directly to stacked Herschel flux densities in GOODS-Herschel and found that the attenuation and reddening of the slope agree with previous results calibrated from local starburst galaxies.…”
Section: Rest-frame Ultraviolet and Optical Spectral Characterizationmentioning
confidence: 89%
“…The constraints induced by the observed correlation between the UV spectral slope, β UV , and the ratio of observed infrared to UV luminosity, IRX 39 , with the flux uncertainties and β UV slope uncertainties included, are also shown in Extended Data Fig. 5.…”
Section: Emission Line Flux Detection Limitsmentioning
confidence: 99%
“…11 It is therefore a valid tool to study the ISM column density of galaxies (Meurer et al 1999;Kong et al 2004;Casey et al 2014). Furthermore, β is the only estimate of the dust content available for the vast majority of galaxies at z>3 due to the relative insensitivity of contemporary optical and IR surveys.…”
Section: Measurements and Simulationsmentioning
confidence: 99%